POLIGAMI : PENAFSIRAN SURAT AN NISA’ AYAT 3 - Rahmi Bakhtiar (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This paper discusses polygamy in the perspective of the Qur’an, which is contained in the letter of an-Nisa, 4:3 and 129. Polygamy is allowed by the Qur’an. Illat (because) the permissibility of polygamy is not driven by a sexual motivation or biological comfort, but by motivation religious, social, and humanity for the purpose of religious and social benefit and accompanied by fair condition among the wives. Although polygamy is allowed, but it should be underlined that the Qur’an suggests polygamy great potential to cause injustice. Hence the principle in the Qur’an is a monogamous marriage. Polygamy is similar to an aircraft emergency exit that can only be opened in an emergency.